2017
DOI: 10.1007/s00359-017-1224-2
|View full text |Cite
|
Sign up to set email alerts
|

On the role of brain aromatase in females: why are estrogens produced locally when they are available systemically?

Abstract: The ovaries are often thought of as the main and only source of estrogens involved in the regulation of female behavior. However, aromatase, the key enzyme for estrogen synthesis, although it is more abundant in males, is expressed and active in the brain of females where it is regulated by similar mechanisms as in males. Early work had shown that estrogens produced in the ventromedial hypothalamus are involved in the regulation of female sexual behavior in musk shrews. However, the question of the role of cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 201 publications
3
28
0
Order By: Relevance
“…In the brain, aromatase may play a pivotal role as it was shown that oestrogen is required for the maintenance, survival and the integrity of dopaminergic neurons [74,75]. Aromatization was also recently highlighted to be key for memory and learning in female organisms, which is mediated through both genomic and non-genomic actions of oestrogen [76]. Xenobiotics, which affect the conversion of oestrogen to testosterone and alter the T/E2 ratio, can therefore have a significant impact on brain health and disease [77].…”
Section: Effects On Murine Brain Gene and Protein Expression Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain, aromatase may play a pivotal role as it was shown that oestrogen is required for the maintenance, survival and the integrity of dopaminergic neurons [74,75]. Aromatization was also recently highlighted to be key for memory and learning in female organisms, which is mediated through both genomic and non-genomic actions of oestrogen [76]. Xenobiotics, which affect the conversion of oestrogen to testosterone and alter the T/E2 ratio, can therefore have a significant impact on brain health and disease [77].…”
Section: Effects On Murine Brain Gene and Protein Expression Levelsmentioning
confidence: 99%
“…An in vitro study pointed out that already at femtomole exposure to TCDD significantly decreased E2 secretion and mRNA expression levels of aromatase were detected in human luteinizing granulosa cells [79]. Interestingly, similar to PPAR-α, which regulates β-oxidation, aromatase activity is also regulated by Ca 2+ , which strongly inhibits aromatase at high but still physiological concentrations [76]. HBCD, CB-153 and TCDD have previously been reported to disrupt Ca 2+ homeostasis [12,18,80,81].…”
Section: Effects On Murine Brain Gene and Protein Expression Levelsmentioning
confidence: 99%
“…This enzyme has now been discovered in several other brain regions. Under physiological conditions, aromatase is constitutively expressed in the neurons of reptiles, birds, and mammals ( 35 ). In mammals, CYP19 expression/aromatase activity has been detected in the hypothalamus, medial preoptic area, bed nucleus of stria terminalis (BST), MeA, prefrontal cortex, hippocampus, and cerebellum ( 35 , 39 46 ).…”
Section: Aromatase Expression In the Brain: A Brief Historymentioning
confidence: 99%
“…Under physiological conditions, aromatase is constitutively expressed in the neurons of reptiles, birds, and mammals ( 35 ). In mammals, CYP19 expression/aromatase activity has been detected in the hypothalamus, medial preoptic area, bed nucleus of stria terminalis (BST), MeA, prefrontal cortex, hippocampus, and cerebellum ( 35 , 39 46 ). Various brain regions of birds tend to express higher amounts of aromatase than in mammals, and thus avian models have greatly expanded our knowledge of how this enzyme regulates cognitive and other behavioral processes ( 35 ).…”
Section: Aromatase Expression In the Brain: A Brief Historymentioning
confidence: 99%
See 1 more Smart Citation